Revolutionary Approach for Fusion of the Classic, Relativity and Quantum field Theories: Sayed’s Acceleration Equation and Probable Violation of E=mc2 - El-Mongy, Sayed A. (JOURNAL OF ADVANCES IN PHYSICS, 2021)
Expansion of the universe is a divine fact in the glorious Quran. The accelerated expansion of the universe is one of the physics mysteries and challenges. This article is a try to find an answer to this ambiguity. A simple fusion and merging of the Newton, Einstein and quantum field equations were carried out to clarify this topic. Innovative equations correlating the acceleration (As), cosmological constant (Ʌ), vacuum energy density (ρ) and distance (d) was deduced. It can be concluded that Sayed`s acceleration constant (As) is proportional to (Ʌ/ρ), (1/8mc2) and (1/πd2). The derivative equation reveals a probable violation of the mass-energy formula (E= mc2); the speed of light might be 12.5% more. This disparity may be due to antimatter contribution; neutrino-antineutrino, β-β+ annihilation and/or a predicted unrecognized very light particle in the atom nucleus. The Sayed`s acceleration constant (As) and (As/Ʌ) ratio were calculated and found to be 6.33825x10-8 m/s2 and 5.7620475x10+44 m3/s2 respectively. Using Sayed`s equations, the calculated acceleration in planck scale is matched with the declared 5.56081x1051 m/s2 value. The The calculated recession velocity at 1 Mpc was found to be 6.5192677 x 108 m/s .and the cosmological constant (Ʌ) is as measured;~1.1x10-52 m-2